PENINGKATAN HASIL BELAJAR LEMPAR MELALUI PERMAINAN SASARAN PETAK BERANGKA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This watchfulness aim to improve the throwing learning achievement of the fourth grade students of SD NegeriKambangan 03 in Blado in the academic year of 2012/2013 by using numbered target cabin game by usingmedia bar tenis, cone, numbered cabin, mini flag, and raffia. The researcher used classroom action research inconducting the research which was done in two cycles. Subject of this study were the fourth grade students ofSD Negeri Kambangan 03 in Blado in the academic year of 2012/ 2013. There were 21 students in which 14of them were male and 7 of them were female. Technique of collecting data which was used were observationtest ability, understanding, and research of learning achievement. Ability test technique was done to find outthe students’ work score in cycle one, cycle two by observing the systematic in doing the throwing motion seriesby modifying the game. The students’ average score was counted to find out the classical achievement as thetarget made. Then, it was made the description of the success of learning marked by the improvement ofstudents’ skill in doing throwing without the feeling of bored. The classical minimum score in cycle oneachieved 81%, in cycle two the improvement achieved 95%. It can be concluded that the use of numbered targetcabin game could improve the throwing learning achievement for the fourth grade students of SD NegeriKambangan 03 in Blado in the academic year of 2012/2013.